The “Learning Service: of Service-Learning: An Exploratory Study in a Business Ethics Course Context - Driscoll, Cathy; McKee, Margaret C.; Price, Shelley T. (Journal of Leadership, Accountability and Ethics, 2017)
Drawing on our teaching and learning experiences and work with community-based service-learning projects over the years, we explore how students are able to learn the value of service to other through service-learning. Qualitative analysis is used to better understand how students are able to learn for, with, and through community. In particular, multiple levels and nestings of community connections appear to help students feel a deeper and more meaningful connection to course learning, team and classmates, school and university, local community, global community, and transcendent purpose